Light-Trap Catch of the Harmful Moths Depending of Moonlight in North Carolina and Nebraska States of USA. (19th November 2012) - Nowinszky, László; Puskás, János
Abstract : The present study discusses the light trapping of harmful insects depending on the moonlight, its polarized percentage, and the moon phases. The trapping data were taken from light traps of North Carolina and Nebraska States of USA. We examined five species. The maximum individual number of species was collected at new moon or near the first quarter and last quarter. The farmers can use our results to forecast their plant protecting works.